Time course of heat acclimation and its decay - Pandolf, K. B. (International Journal of Sports Medicine, 1998)
More is known about the time course for the acquisition of human heat acclimation during exercise than its decay or loss. Pioneering research in the 1940s led to our early understanding of the heat acclimation process and its subsequent decay with further knowledge concerning the associated physiological mechanisms in later years. For both hot-dry and hot-humid environments, nearly complete exercise-heat acclimation occurs after 7 to 10 days of exposure. However, about two-thirds to 75% of the physiological adjustments and improvements in performance are seen in 4 to 6 days. Individuals with high levels of aerobic fitness are partially but not fully acclimated to the heat. Most of the early studies on decay or loss of heat acclimation are flawed by very small samples, incomplete heat acclimation or inappropriate measurements. Nevertheless, these studies are pioneering in a sense because they indicate that the retention of heat acclimation is quite variable between individuals and environments. Retention of the benefits of heat acclimation appears to remain longer for dry compared to humid heat. High levels of aerobic fitness seem associated with greater retention of heat acclimation. Further well-designed and definitive studies on decay or loss of heat acclimation appear necessary.